The role of self-compassion in the well-being of self-identifying gay men. Issue 1 (2nd January 2017) - Beard, Kieron; Eames, Catrin; Withers, Paul
ABSTRACT: The psychological literature has identified many benefits of self-compassion. In an effort to explore self-compassion as a potential resource for gay men, we explored relationships between self-compassion, well-being, self-esteem, pride (authentic and hubristic), attachment, and two minority-specific processes, outness and internalized heterosexism. A sample of predominantly White, self-identifying gay men (N = 139) completed an online survey consisting of demographic variables and questionnaires related to these constructs. Authentic pride, self-esteem, self-compassion, and outness were significantly positively related to well-being. Avoidant and anxious attachment styles and internalized heterosexism were significantly negatively related to well-being. No relationship was found between hubristic pride and self-compassion, or well-being. Multiple linear regression analysis revealed that the self-compassion components of self-kindness and isolation, the gay affirmation component of internalized heterosexism, outness, and the avoidance and anxiety components of attachment were significant predictors of general well-being. Results suggest that, in addition to developing an authentic sense of pride, self-compassion may be beneficial in cultivating well-being in gay men.